Plasticised polymer electrolytes based on PMMA grafted natural rubber-LiCF3SO3-PEG200 - Yap, K.S.; Teo, L.P.; Sim, L.N.; Majid, Siti Rohana; Arof, Abdul Kariem (Springer Verlag (Germany), 2011)
Polymer electrolyte membranes that consist of 70 wt-% natural rubber grafted with 30 wt-% poly(methyl methacrylate) (MG30) and 30 wt-% lithium trifluoromethane sulphonate (LiTf) salt have been investigated with various concentrations of poly(ethylene glycol) 200 (PEG200). The formation of polymer-salt complexes has been confirmed by Fourier transform infrared spectral studies. X-ray diffraction studies further confirmed that all the samples prepared are amorphous. The highest conducting sample has the composition of 63 wt-% MG30-27 wt-% LiTf-10 wt-% PEG with conductivity of 3.65 x 10(-4) S cm(-1) at 298 K. From differential scanning calorimetry studies, the glass transition temperature T-g is found to increase from -63 to -54 degrees C with the increase in PEG concentration at 30 wt-% PEG200. The ionic transference number of mobile ions has been estimated using Wagner's polarisation method, and the results reveal that the conducting species are mainly ions.